2018
DOI: 10.3389/fnhum.2018.00199
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Self-Referential Processing on Attentional Orienting in Frontoparietal Networks

Abstract: Self-referential processing refers to the processing of information relevant to oneself and plays an important role in cognition. Behavioral studies have shown that directional cue stimuli have a qualitatively different function during attentional orienting after presentation of the cue associated with the self. However, it is necessary to determine how neural activity is influenced by self-referential processing during attentional orienting. The present study involved establishing an association between non-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“… Wei et al (2017) , for example, have explored how a cohort of adults exposed to the Tianjin explosion incident exhibited greater activation of the left hemisphere of the dorsolateral prefrontal cortex (L dlPFC), which they identify as a crucial region of interest (ROI) implicated in PTG because it regulates distressing affect and irregular heart rate. Similar findings about the L dlPFC were presented by Nakagawa et al (2016) after assessing survivors of the East Japan Great Earthquake, adding that activation of both hemispheres of the anterior cingulate cortex (L/R ACC) was similarly important because these ROIs help individuals with the synthesis of thoughts and feelings into a self-referential worldview and belief system ( Yoshimura et al, 2009 ; Yang et al, 2012 ; Nejad et al, 2013 ; Wagner et al, 2015 ; Zhao et al, 2018 ). One might observe that highlighting the L dlPFC over other prefrontal brain regions in the process of PTG may appear odd because it is often the ventromedial prefrontal cortex (vmPFC) that facilitates self-referential cognition in humans ( D’Argembeau, 2013 ; Konu et al, 2020 ; Park et al, 2020 ; Stendardi et al, 2021 ; Yin et al, 2021 ).…”
Section: Introductionsupporting
confidence: 53%
“… Wei et al (2017) , for example, have explored how a cohort of adults exposed to the Tianjin explosion incident exhibited greater activation of the left hemisphere of the dorsolateral prefrontal cortex (L dlPFC), which they identify as a crucial region of interest (ROI) implicated in PTG because it regulates distressing affect and irregular heart rate. Similar findings about the L dlPFC were presented by Nakagawa et al (2016) after assessing survivors of the East Japan Great Earthquake, adding that activation of both hemispheres of the anterior cingulate cortex (L/R ACC) was similarly important because these ROIs help individuals with the synthesis of thoughts and feelings into a self-referential worldview and belief system ( Yoshimura et al, 2009 ; Yang et al, 2012 ; Nejad et al, 2013 ; Wagner et al, 2015 ; Zhao et al, 2018 ). One might observe that highlighting the L dlPFC over other prefrontal brain regions in the process of PTG may appear odd because it is often the ventromedial prefrontal cortex (vmPFC) that facilitates self-referential cognition in humans ( D’Argembeau, 2013 ; Konu et al, 2020 ; Park et al, 2020 ; Stendardi et al, 2021 ; Yin et al, 2021 ).…”
Section: Introductionsupporting
confidence: 53%
“…The precuneus is involved in emotion regulation, self-agency, and self-referential processing: the spontaneous causal attributions (self-agency or lack of self-agency) that an individual makes in relation to events that elicit positive and negative emotions ( Loeffler et al, 2018 ). Self-referential processing also affects episodic memory: the recall of memories is better when it is related to the self ( Zhao et al, 2018 ). Of particular interest here is a recent EEG study showing the precuneus to be overactive in children with mixed FND ( Kozlowska et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apps et al ( 2012 , 2015 ) have found that a set of unimodal and multimodal areas are sensitive to self-adulthood identification. It has been shown that fronto-parietal attentional networks could be recruited by the presence of self-related stimuli (Humphreys and Sui 2016 ; Zhao et al 2018 ). Hence, the role of the inferior parietal areas deserves more dedicated studies to clarify whether it entails a static representation of the physical identity.…”
Section: Introductionmentioning
confidence: 99%